2014
DOI: 10.1175/waf-d-14-00056.1
|View full text |Cite
|
Sign up to set email alerts
|

A Polarimetric and Microphysical Investigation of the Northeast Blizzard of 8–9 February 2013

Abstract: On 8-9 February 2013, the northeastern United States experienced a historic winter weather event ranking among the top five worst blizzards in the region. Heavy snowfall and blizzard conditions occurred from northern New Jersey, inland to New York, and northward through Maine. Storm-total snow accumulations of 30-61 cm were common, with maximum accumulations up to 102 cm and snowfall rates exceeding 15 cm h 21 . Dual-polarization radar measurements collected for this winter event provide valuable insights into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 37 publications
2
13
0
Order By: Relevance
“…The observed lightning flashes were located downstream of high value of reflectivity core (> 35 dBZ) and higher reflectivity aloft, which are ascribed by graupel. Griffin et al () found exceptionally high value of Z H (>55 dBZ) and corresponding enhanced differential reflectivity during 2013 northeast United States winter blizzard. Those enhanced differential reflectivity indicated the updraft and generation of the supercooled water in the convective storms that are associated with atmospheric electrification.…”
Section: Discussionmentioning
confidence: 99%
“…The observed lightning flashes were located downstream of high value of reflectivity core (> 35 dBZ) and higher reflectivity aloft, which are ascribed by graupel. Griffin et al () found exceptionally high value of Z H (>55 dBZ) and corresponding enhanced differential reflectivity during 2013 northeast United States winter blizzard. Those enhanced differential reflectivity indicated the updraft and generation of the supercooled water in the convective storms that are associated with atmospheric electrification.…”
Section: Discussionmentioning
confidence: 99%
“…The historic 8-9 February 2013 northeastern blizzard has been studied extensively (Griffin et al 2014;Picca et al 2014;Ganetis and Colle 2015), and produced some of the most extreme winter storm polarimetric radar signatures thus far observed (Griffin et al 2014). This includes vigorous planar crystal growth regions called dendritic growth zones (DGZs) in the literature, which polarimetric radars can detect as enhancements of specific differential phase K DP and/or differential reflectivity Z DR near 2158C (Kennedy and Rutledge 2011; Andrić et al 2013;Bechini et al 2013;Schneebeli et al 2013;Schrom et al 2015).…”
Section: B 8-9 February 2013mentioning
confidence: 99%
“…Further, intense coastal lows often produce high winds and waves that can damage coastal structures (Picca et al 2014). Recent blizzards labeled as ''historic'' have individually cost tens of millions of dollars in damage and significant loss of life (e.g., Griffin et al 2014;Picca et al 2014). Even when major cities are spared the extreme weather, there can be an enormous economic toll: an estimated $200 million was lost in January 2015 when New York City (NYC) shut down its transit system based on forecasts of a major snow event (Dokoupil 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations